World Trade in Services : Evidence from A New Dataset - Loungani, Prakash (IMF Working Papers; Working Paper ;, 2017)
Using a newly constructed dataset on trade in services for 192 countries from 1970 to 2014, this paper shows that services currently constitute one-fourth of world trade and an increasingly important component of global production. A detailed analysis of patterns and stylized facts reveals that exports of services are not only gaining strong momentum and catching up with exports of goods in many countries, but they could also trigger a new wave of trade globalization. Research applications of the trade in service dataset on structural transformation, resilience, labor reallocation, and income distribution are outlined.